Narratives of Gestational Diabetes Provide a Lens to Tailor Postpartum Prevention and Monitoring Counseling. (22nd June 2020) - Gunn, Christine; Bernstein, Judith; Bokhour, Barbara; McCloskey, Lois
Abstract : Introduction: Women with gestational diabetes mellitus (GDM) have a marked increased risk of early onset type 2 diabetes, but less than half initiate postpartum glucose testing or connect with a primary care provider for continued follow‐up after giving birth. This study analyzed women's narratives about their GDM‐affected pregnancies to (1) identify different patterns (narrative archetypes) that capture the GDM experience; (2) explore how these patterns relate to awareness of ongoing risk after pregnancy and affect participation in self‐care, monitoring, and preventive health care going forward; and (3) explore the use of identified patterns to tailor conversations with patients during prenatal and postpartum care to their actual perceptions and concerns about future risk. Methods: Open‐ended interviews elicited women's experiences and perspectives about GDM and its management. A narrative analysis first identified segments of text related to risk and behaviors and then applied Frank's narrative archetypes (restitution, chaos, quest) as an interpretive lens. Results: Interviews were completed in English (n = 15), Spanish (n = 7), and Haitian Creole (n = 7). We found distinct patterns: stories of restitution (n = 13), quest (n = 4), chaos (n = 4), and mixed narratives (n = 7). Using these archetypes, we found differences in how women respond to challenges related to disease complexity, treatment, and future risks. These patterns led to marked differences in the steps women took to prevent early onset type 2 diabetes. Discussion: Frank's narrative types provided insight into women's responses to clinical protocols, health care advice, and subsequent prevention actions. A restitution pattern may result in premature closure and lack of awareness of risk. Similarly, a chaos pattern may contribute to a sense of helplessness to implement follow‐up recommendations, despite risk awareness. Understanding these patterns can help clinicians tailor individualized support as women transition from GDM with its focus on a healthy fetus and newborn to preventive self‐care to protect their health.